The Philippines from ‘People Power’ to democratic backsliding - Thompson, Mark R. (Cambridge, United Kingdom Cambridge University Press, 2023)
"This Element explores how in the Philippines a “whiggish” narrative of democracy and good governance triumphing over dictatorship and kleptocracy after the “people power” uprising against Ferdinand E. Marcos in 1986 was upended by strongman Rodrigo R. Duterte three decades later. Portraying his father’s authoritarian rule as a “golden age,” Ferdinand R. Marcos, Jr. succeeded Duterte by easily winning the 2022 presidential election, suggesting democratic backsliding will persist. A structuralist account of the inherent instability of the country’s oligarchical democracy offers a plausible explanation of repeated crises but underplays agency. Strategic groups have pushed back against executive aggrandizement. Offering a “structuration” perspective, presidential power and elite pushback are examined as is the reliance on political violence and the instrumentalization of mass poverty. These factors have recurrently combined to lead to the fall, restoration, and now steep decline of democracy in the Philippines."
Keywords: Philippines -- Politics and governance -- 21st century; Philippines -- Social condition -- 21st century; Philippines -- Economic conditions -- 21st century